Defending hash tables from algorithmic complexity attacks with resource burning - Chakraborty, Trisha; Saia, Jared; Young, Maxwell (Theoretical computer science, 2024)
We consider the problem of defending a hash table against a Byzantine attacker that is trying to degrade the performance of query, insertion and deletion operations. Our defense makes use of resource burning (RB)—the verifiable expenditure of network resources—where the issuer of a request incurs some RB cost. Our algorithm, Depth Charge, charges RB costs for operations based on the depth of the appropriate object in the list that the object hashes to in the table. By appropriately setting the RB costs, our algorithm mitigates the impact of an attacker on the hash table's performance. In particular, in the presence of a significant attack, our algorithm incurs a cost which is asymptotically less that the attacker's cost.